2020
DOI: 10.5222/jaren.2020.82435
|View full text |Cite
|
Sign up to set email alerts
|

The Attitude of Healthcare Professionals Towards Disabled Individuals

Abstract: Objective: The aim is to investigate the attitudes of healthcare professionals in Istanbul towards people with disabilities within the scope of the "Be Happy in Life" project, which is conducted under the coordination of Istanbul Provincial Health Directorate with the aim of increasing the well-being of the disabled and their families and professionals. Method: This study is a descriptive study on healthcare professionals working in health institutions in Istanbul affiliated with the Ministry of Health. The qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
2
1
Order By: Relevance
“…The findings of this study revealed that the participants had a fair level of knowledge, attitude, and perception of disability. This is contrary to some previous studies that found that medical students and health professionals have low levels of knowledge and attitude [20][21][22][23]. Differences in the study populations and the types of instruments utilized could explain the contradictory results found in this study and the results from previous researchers.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The findings of this study revealed that the participants had a fair level of knowledge, attitude, and perception of disability. This is contrary to some previous studies that found that medical students and health professionals have low levels of knowledge and attitude [20][21][22][23]. Differences in the study populations and the types of instruments utilized could explain the contradictory results found in this study and the results from previous researchers.…”
Section: Discussioncontrasting
confidence: 99%
“…Having more years of experience also had no significant association with having greater knowledge, a good attitude, or a positive perception of physical disabilities. This is in line with previous studies, which found no correlation between knowledge, attitude, and years of work experience [21,23,26]. Some previous studies had reported a negative correlation between health workers attitude, years of experience and physical disabilities [22,28].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations